A case report of long-term survival of metastatic extraskeletal myxoid chondrosarcoma treated with surgery and hypofractionated radiotherapy. Issue 4 (9th July 2014) - Qiu, Haoming; Hare, Mary; Chen, Yuhchyau
Abstract: We describe the case of a patient with a 10-year history of metastatic extraskeletal myxoid chondrosarcoma (EMC), who underwent repeated surgical excision and ten courses of hypofractionated radiotherapy to locally recurrent or metastatic disease. We review the literature on EMC's and propose that surgery and radiotherapy can be used to control disease progression and palliate symptoms for extended periods of time with acceptable toxicity profiles.